Treatment of Dyslipidemia Using CRISPR/Cas9 Genome Editing - Chadwick, Alexandra C. (Curr Atheroscler Rep, 2017)
PURPOSE OF REVIEW: Clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated 9 (Cas9) has recently emerged as a top genome editing technology and has afforded investigators the ability to more easily study a number of diseases. This review discusses CRISPR/Cas9’s advantages and limitations and highlights a few recent reports on genome editing applications for alleviating dyslipidemia through disruption of proprotein convertase subtilisin/kexin type 9 (PCSK9). RECENT FINDINGS: Targeting of mouse Pcsk9 using CRISPR/Cas9 technology has yielded promising results for lowering total cholesterol levels, and several recent findings are highlighted in this review. Reported on-target mutagenesis efficiency is as high as 90% with a subsequent 40% reduction of blood cholesterol levels in mice, highlighting the potential for use as a therapeutic in human patients. SUMMARY: The ability to characterize and treat diseases is becoming easier with the recent advances in genome editing technologies. In this review, we discuss how genome editing strategies can be of use for potential therapeutic applications.